2021
DOI: 10.1155/2021/4688764
|View full text |Cite
|
Sign up to set email alerts
|

Pachychoroid Spectrum Disorder Findings in Patients with Coronavirus Disease 2019

Abstract: Purpose. To report the occurrence of acute, bilateral, central serous chorioretinopathy (CSC), and pachychoroid spectrum disorder findings in patients with coronavirus disease 2019 (COVID-19). Methods. In recovered cases of COVID-19 with visual disturbances, complete ocular examinations with multimodal retinal and choroidal evaluation, including enhanced depth imaging optical coherence tomography, fluorescein or indocyanine green angiography, and blue autofluorescence, were obtained. Results. Four COVID-19 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In the first report, all three cases improved after treatment, two cases with steroidal anti mineralocorticoid and one case by photodynamic therapy. 22 In the second article, the patient improved without treatment. 23…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the first report, all three cases improved after treatment, two cases with steroidal anti mineralocorticoid and one case by photodynamic therapy. 22 In the second article, the patient improved without treatment. 23…”
Section: Discussionmentioning
confidence: 94%
“…Few previously reported studies have described the development of CSC in COVID-19. Abrishami et al reported three cases of bilateral CSC 22 and Amulya and Thanuja one unilateral case, 23 all not associated with corticosteroid use. In the first report, all three cases improved after treatment, two cases with steroidal anti mineralocorticoid and one case by photodynamic therapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These vessels may have a direct impact on outer retina perfusion by mechanically compressing inner choroidal layers and inducing choriocapillaris ischemia as seen on indocyanine angiography imaging. Pachychoroid phenotype with hyperpermeability and congestion of the choroidal vasculature can be observed or exacerbated in the setting of COVID-19 [25].…”
Section: Introductionmentioning
confidence: 99%
“…Ocular surface, as well as corneal signs and symptoms, was reported, and the most prevalent manifestations were conjunctivitis and dry eye [ 2 , 3 ]. Posterior segment involvements were numerous as cotton wool spots, retinal hemorrhages, dilated and tortuous vessels, decreased retinal microvasculature, ischemic retinal involvements, pachychoroid spectrum presentations, chorioretinitis, and optic nerve head involvement [ 4 7 ]. Furthermore, neuroinvasive actions of the virus were reported in previous studies [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%